"I deserve to be in the loop": A Mixed Methods Study of Young Women's Experiences of Pregnancy Care in NSW. (September 2022) - Doust, Jenni; Burns, Elaine; Sheehan, Athena; Psaila, Kim
Abstract : Introduction: Pregnancy interrupts the traditional trajectory of a young woman when they are suddenly placed on an accelerated physical and emotional developmental pathway, simultaneously towards adulthood and motherhood. The Australian rate of young women pregnancy is at an all-time low. However, the smaller number of young pregnant women are very vulnerable individuals in Australian population. Pregnancy care is known to influence positive outcomes for women and babies. There has been an increased engagement of care by pregnant women before 20 weeks of 61.8% in 2018, although, young women aged 24 years and under, the rate is halved to that of their older peers. Little is known about the care and experiences that young pregnant women access in NSW and whether care meets their needs. Aim: To determine the experiences of young pregnant women, aged 16-24 years, when accessing pregnancy care services in NSW. Methods: A sequential mixed method design. Quantitative data collection - online survey achieving a total of 101 participants. Qualitative data collection – follow up in-depth interviews of eight young women's herstory. The two data sets were integrated to reveal overall findings. Results: The integrated findings provided rich insights into the overall picture of what young pregnant women in NSW are faced with when becoming a mum. Young women intrinsically want to be good mums however they experience multiple social hardships and mental health concerns, as well as stigma from maternity care provider's and society. Having a known care provider had a` profound impact on the way they felt supported during their journey to motherhood. Conclusion: This study represents a call to action and break the intergenerational cycle of psychological and social hardships faced by young pregnant women and widespread stigma within maternity care. Pregnancy care in NSW is not meeting young pregnant women needs and must be addressed.